The Effect of Project-Based Learning (PjBL) Models and Their Variations on Student Learning Outcomes and Motivation - Isyatun Rodiah; Rahma Dani (Master of Physics Education Study Programme, 2025)
This study aims to comprehensively analyze the impact of implementing Project-Based Learning (PjBL) and its variations on students’ learning outcomes and motivation. A state-of-the-art review method was employed by examining research articles published between 2017 and 2023. The findings indicate that PjBL and its variations—such as multimedia-assisted PjBL, STEM integration, gamification, and digital technology-based approaches like AR and Quizizz—consistently have a positive influence on students’ learning outcomes, motivation, and critical as well as creative thinking skills. Nevertheless, existing studies still face limitations, including restricted scope, small sample sizes, and limited instrument validity. This review provides a comprehensive map of current research and highlights opportunities for future studies to design more adaptive and contextual PjBL implementations.